O cotidiano e a pandemia da Covid-19 na perspectiva das crianças - Camargo, Ana Paula (Universidade Federal de São Carlos, 2023)
The Covid-19 pandemic and the emergency measures taken to control and combat the virus have significantly impacted people's lives, with children being one of the most affected social groups. Despite not being the focus of greater concern for being considered a "lower risk" group for contagion and death, literature points to the need to pay attention to the pandemic's impacts on children's development and mental health, especially in situations of greater inequality and social vulnerability. Thus, it is essential to conduct investigations that seek to understand this new and emerging daily life experienced by different social groups in distinct contexts and scenarios. It is considered that from this panorama, it is possible not only to measure and demarcate a historical and social context of much suffering, loss, and struggle, but primarily, to understand the possibilities of creation and life, day after day. Therefore, the objective of this study was to understand how children experienced daily life during the Covid-19 pandemic from their own perspective. In addition, it sought to identify what may have been positive or difficult during the pandemic, according to the children themselves. This is an exploratory study, using a qualitative approach, conducted with 19 children aged 9 to 11 years old, linked to a public school in a medium-sized city in the interior of São Paulo State. Graphic elucidation was used as a trigger for the theme's collection of data, followed by a semi-structured interview. Interpretive analysis was not sought for graphic elucidations, but rather to understand them based on the children's own verbalizations. Both the narratives derived from graphic elucidations and the data produced in interviews were analyzed using thematic analysis. Seven themes emerged from the graphic elucidations and interviews: Children's understanding of Covid-19 and the feelings generated; death and mourning due to the Covid-19 pandemic; play as the main activity in children's daily life; the use of screens during the Covid-19 pandemic; school and children's learning during the Covid-19 pandemic; family relationships during the Covid-19 pandemic; and the social vulnerability experienced by families during the Covid-19 pandemic. The results showed how clear children are about the virus's origin and spread, the safety and protection measures adopted, the risks arising from contamination, and future expectations with the emergence of the vaccine. Furthermore, the children explained what Covid-19 and the pandemic were like based on daily changes and actions, such as the sudden suspension of school activities and the use of masks. In this direction, regarding daily activities during the pandemic, it was identified that playing continued to be present, based on children's inventiveness, and given isolation, playing took place mainly outdoors, with animals, with adaptations to maintain distancing from their peers. It is pointed out that their daily lives also changed in relation to access to school and the right to education, so that they were able to follow, perform proposed activities and learn remotely little, considering the absence of electronic equipment and access to the internet. Another identified change refers to family dynamics and relationships. In some families, the relationship and closeness between members intensified, and they were able to share more moments together, while in others, there was distancing, conflicts, and reports of violence. It is understood that the results of this study, obtained from the experience and daily life perspective of the children themselves, demonstrate how much children have been affected by the pandemic. In this direction, it is hoped that the collected data may contribute to greater knowledge of one of the greatest health crises ever experienced, which is being reinvented day after day, favoring new reflections and discussions about public policies and intervention strategies aimed at this population.

El escenario de la pandemia del Covid-19 y las medidas de emergencia para controlar y combatir la propagación del virus impactaron significativamente en la vida de las personas, por lo que los niños fueron uno de los grupos sociales más afectados. Si bien no son el foco de mayor preocupación por ser considerados un grupo con “menor riesgo” de contagio y muerte, la literatura apunta a la necesidad de prestar atención a los impactos de la pandemia en su desarrollo y salud mental, especialmente en situaciones de mayor riesgo, desigualdad y vulnerabilidad social. De esta manera, es fundamental realizar investigaciones que busquen comprender esta nueva y emergente cotidianidad, vivida por diferentes grupos sociales en diferentes contextos y escenarios. Se considera que desde este panorama es posible no sólo dimensionar y demarcar un contexto histórico y social de mucho sufrimiento, pérdidas y luchas, sino principalmente, comprender las posibilidades de creación y de vida, día tras día. Por lo tanto, el objetivo de este estudio fue comprender cómo los niños experimentaron la vida cotidiana en la pandemia de Covid-19, desde su propia perspectiva. Además, buscó identificar lo que pudo haber sido positivo o difícil en la pandemia, según la opinión de los propios niños. Se trata de un estudio exploratorio, con abordaje cualitativo, realizado con 19 niños de 9 a 11 años, vinculados a una escuela pública de una ciudad de mediano porte del interior del Estado de São Paulo. Para la recolección de datos, se utilizó la elucidación gráfica como disparador del tema y, posteriormente, una entrevista semiestructurada. Para las elucidaciones gráficas no se buscó un análisis interpretativo, sino comprenderlas a partir de las propias verbalizaciones de los niños. Tanto las narrativas surgidas de las elucidaciones gráficas como los datos producidos en las entrevistas fueron analizados a partir del análisis temático. Siete temas surgieron de los análisis: la comprensión de los niños sobre el Covid-19 y los sentimientos generados; muerte y luto a consecuencia de la pandemia; el juego como actividad principal en la vida cotidiana de los niños; el uso de pantallas; la escuela y el aprendizaje de los niños; las relaciones familiares y la vulnerabilidad social que viven las familias. Los resultados mostraron la claridad de los niños sobre el origen del virus y su propagación, las medidas de seguridad y protección adoptadas, los riesgos derivados de la contaminación y las expectativas de futuro con la aparición de la vacuna. Además, los niños explicaron cómo fue el Covid-19 y la pandemia a partir de cambios y acciones cotidianas, como, por ejemplo, la suspensión repentina de las actividades escolares y el uso de mascarillas. En esa dirección, en cuanto a las actividades cotidianas durante la pandemia, se identificó que el juego siguió estando presente, a partir de la inventiva de los niños, y ante el aislamiento, el juego se dio principalmente en ambientes al aire libre, con animales, con adaptaciones para mantener distancia de sus compañeros. Se señala que su cotidiano también cambió en relación al acceso a la escuela y al derecho a la educación, por lo que no pudieron seguir, realizar las actividades propuestas y aprender a distancia, considerando la ausencia de equipos electrónicos y acceso a internet. Otro cambio identificado se refiere a la dinámica y las relaciones familiares. En algunas familias se intensificó la relación y cercanía entre los miembros y pudieron compartir más momentos juntos y, en otras, hubo distanciamiento, conflictos y denuncias de violencia. Se entiende que los resultados del presente estudio, obtenidos de la experiencia y vivencia del cotidiano desde la perspectiva del niño, muestran cuánto fueron y han sido afectados los niños por la pandemia. En esa dirección, se espera que los datos recolectados puedan contribuir a una mayor comprensión de una de las mayores crisis de salud jamás vivida, favoreciendo nuevas reflexiones y discusiones sobre políticas públicas y estrategias de intervención dirigidas a esta población.
Daily life and the Covid-19 pandemic from the perspective of children
La vida cotidina y la pandemia del Covid-19 desde la perspectiva de los ninõs
Keywords: Children; Daily life; Mental health; Occupational therapy; Covid-19; Crianças; Cotidiano; Saúde mental; A diario; Ninõs; Salud mental; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL